1999
DOI: 10.1044/0161-1461.3002.196
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Four Vocabulary Tests Administered to Preschool-Age Children

Abstract: This study examined the empirical evidence for using four vocabulary tests (Peabody Picture Vocabulary Test-III [Dunn & Dunn, 1997], Receptive One-Word Vocabulary Test [Gardner, 1985], Expressive Vocabulary Test [Williams, 1997], Expressive One-Word Vocabulary Test-Revised [Gardner, 1990]) to screen or identify specific language impairment (SLI) in preschool-age children. Tests were administered to 31 4- and 5-year-old children with SLI and 31 age-matched controls with normal language (NL). All children spoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(128 citation statements)
references
References 17 publications
7
104
2
7
Order By: Relevance
“…First, expressive vocabulary was evaluated by way of the Expressive OneWord Picture Vocabulary Test (third edition), a standardized and validated test of expressive vocabulary in pre-school children. 16,17 Scores were compared with age-appropriate norms and converted into centiles. Form and use (pragmatics) of language, although assessed in the clinic, were not scored objectively and thus could not be retained in the analysis.…”
Section: Developmental Assessmentmentioning
confidence: 99%
“…First, expressive vocabulary was evaluated by way of the Expressive OneWord Picture Vocabulary Test (third edition), a standardized and validated test of expressive vocabulary in pre-school children. 16,17 Scores were compared with age-appropriate norms and converted into centiles. Form and use (pragmatics) of language, although assessed in the clinic, were not scored objectively and thus could not be retained in the analysis.…”
Section: Developmental Assessmentmentioning
confidence: 99%
“…We employed classification analysis in order to examine the diagnostic accuracy of each measure and the measures in combination. This procedure entails calculating how well individual children are classified by the language measure, rather than estimating whether children as a group demonstrate significantly different test score means (Gray, Plante, Vance, & Henrichsen, 1999). Plante and Vance (1994) suggested that language tests that discriminate between children with and without language impairment with an accuracy above 90% are considered "good" discriminators and those that discriminate with an accuracy between 80 and 90% are considered "fair" discriminators.…”
Section: Classification Efficacy Of Dynamic and Static Measuresmentioning
confidence: 99%
“…The PPVT measures language abilities as an example of vocabulary knowledge with children as young as age two. Studies using the PPVT indicated that kindergarten children can identify correct words by pointing at pictures [22]. Picture interview designs have been used in studies measuring children's environmental knowledge [15].…”
Section: Table 1 Case Study Sample (N = 98)mentioning
confidence: 99%